An exploration of factors contributing to multicultural counseling self-efficacy in addiction counselors - Smith, Joshua D. (Journal of addictions & offender counseling, 2023)
A non-experimental, correlational survey design was used to explore relationships between counselor recovery status, training, and counselor demographic variables on multicultural counseling self-efficacy in addiction counselors (N = 283) using the Multicultural Counseling Self-Efficacy – Racial Diversity Form. A multiple-indicators and multiple-causes model analysis indicated significant differences based on race, multicultural education, and CACREP program attendance on multicultural counseling self-efficacy. Implications from this study and recommendations for future research are discussed.